Integrating AI-driven technologies into service marketing - Nadda, Vipin 1970-; Singh, Amrik; Singh, Vipin 1963-; Tyagi, Pankaj Kumar 1979- (Advances in marketing, customer relationship management, and E-services (AMCRMES) book series, 2024)
In an era marked by rapid technological advancements and the increasing integration of artificial intelligence (AI) into various sectors, the intersection of AI technologies with service marketing stands as a pivotal frontier. It is essential to explore the intricate nexus between AI technologies and service marketing strategies.Integrating AI-Driven Technologies Into Service Marketing elucidates the transformative impact of AI on key facets of service marketing, ranging from customer engagement and relationship management to market segmentation and product customization. It underscores the imperative for stakeholders in emerging economies to harness the power of AI technologies in crafting innovative and adaptive service marketing strategies. The book navigates the complexities of AI adoption while offering pragmatic recommendations for fostering responsible and inclusive AI-driven service marketing ecosystems. Covering topics such as customer engagement, influencer marketing, and sentiment analysis, this book is an excellent resource for scholars, researchers, educators, business professionals, managers, academicians, postgraduate students, and more